Fostering Fairy Tale Literacy for Young Readers: The Flipping Javanese Manuscript's Effectivity - Insani, Nur Hanifah; Fuadhiyah, Ucik (International Journal of Multidisciplinary Sciences, 2025)
In today’s digital era, young children are increasingly exposed to a vast array of apps, games, and videos. Amid this digital abundance, an urgent educational need has emerged, particularly for Javanese youth readers to understand how digital formats influence their literacy skills. This study aims to analyze the effectiveness of digital fairy tale flipping manuscripts in supporting the learning process of reading Javanese script texts. A quantitative experimental method was employed, involving a sample of 60 students. Data were collected using a test instrument and a questionnaire developed by the researchers. The test assessed reading ability, while the questionnaire gathered insights on learners’ perceptions and experiences. The findings indicate that the use of digital fairy tales with flipping manuscript features significantly enhances the students’ ability to recognize and read Javanese letters. The interactive nature of the digital format was found to increase engagement, comprehension, and retention compared to traditional methods. In conclusion, this study demonstrates that digital flipping fairy tales can effectively support the learning of Javanese script, offering an innovative and engaging medium for preserving and promoting regional literacy in the digital age.